Frontispiece: Towards Printed Organic Light‐Emitting Devices: A Solution‐Stable, Highly Soluble CuI–NHetPHOS. Issue 46 (2nd November 2016) - Wallesch, Manuela; Verma, Anand; Fléchon, Charlotte; Flügge, Harald; Zink, Daniel M.; Seifermann, Stefan M.; Navarro, José M.; Vitova, Tonya; Göttlicher, Jörg; Steininger, Ralph; Weinhardt, Lothar; Zimmer, Manuel; et al.
Abstract : Printable Binuclear Copper Complexes A thermally activated delayed fluorescence (TADF)‐based OLED device that reached an efficiency of 11±2 % external quantum efficiency (EQE) was achieved using a printable copper complex. For more details, see the Communication by C. Heske, S. Bräse, D. Volz et al. onpage 16400 ff.